Poems related to viticulture in Kakheti - Abuladze, Nana (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
Poems related to viticulture and winemaking are a chronicle of the past. Samples of folk poetic creations allow us to think and comprehend the very diverse and multifaceted life of our ancestors, which leaves an indelible mark on the inner world of man. It is noteworthy the poems preserved in Kakheti, are related to the vineyard, vine, and wine. Kakheti is a cellar of this wonderful plant and soul-pleasing fluid, as well as a united Georgia. The scientific basis of viticulture and winemaking was mainly laid in the XIX century. The scientific study of their history begins from the same period. Modern cultivated vines are derived from wild vines. Viticulture and winemaking have reached a particularly high level of development in Kakheti. Records of labor songs and terms recorded in ancient written monuments and Renaissance writings reveal their antiquity. Mankind has been accompanied by labor since its inception, and labor has been creating its own poetry. One of the important places in labor poetry is occupied by vineyard poems. It was widespread throughout Georgia and was mainly performed collectively. We also have individual performance texts: vineyard bar and pitcher washing. Wine has a special place in the consciousness of Georgians. He is the savior and delicacy of Lkhini, Keif. Vine, wine, and cellar have an honorable place in human life, which is clarified by both folklore and ethnographic material. Vine, wine, and cellar are considered as one whole in the consciousness of Georgians.